Inventário da ictiofauna do alto rio Paraíba do Sul e caracterização molecular das espécies encontradas - Maia, Gláucia Maria Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The state of São Paulo has four main drainages: Paraná river, Paraíba do Sul river, Ribeira do Iguape river and coastal rivers. The Paraíba do Sul river is born in Sao Paulo and drains an important range of land east of the state. Its ichthyofauna has some similarities and many differences from the continental and coastal drainages which highlights the importance of this study. Surveys conducted in the ichthyofauna of this basin, as in other large river basins in Brazil, is still incomplete. Moreover, there is no consensus about the taxonomic status of many species listed in these surveys. Considering the promising use of DNA barcode as a global system for species identification, the present study is aimed to establishing an inventory of the ichthyofauna of the São Paulo portion of the river Paraíba do Sul and simultaneously build a DNA barcode reference sequence library for fish found. Were obtained and analyzed 354 sequences of the gene cytochrome oxidase c subunit I (COI) belonging to 66 species of São Paulo portion of the Paraíba do Sul river. The average K2P distance between individuals within species of this basin was 0.48%, and 9,87% between species within a genus. Five pairs of species (10 species) showed low levels of interspecific genetic divergence (<2%),but all could be correctly identified. This study showed that the fish species analyzed could be identified efficiently through the use of barcode generating data that can provide information for further studies of this fauna, besides contributing to the global initiative to characterize the species of fish in the world of a molecular point of view. Five pairs of species (10 species) showed low levels of interspecific genetic divergence (<2%), but all could be correctly identified. This study showed that the fish species analyzed could be identified efficiently through the use of barcode generating data that can provide subsidies for further studies in this fauna, as well as ...

O Estado de São Paulo apresenta quatro drenagens: Rio Paraná, Rio Paraíba do Sul, Rio Ribeira de Iguape e rios litorâneos. O rio Paraíba do Sul nasce em São Paulo e drena uma importante faixa de terras da região leste do Estado. Sua ictiofauna tem algumas semelhanças e muitas diferenças em relação às drenagens continentais e costeiras o que realça a importância do presente estudo. Os levantamentos ictiofaunísticos realizados nesta bacia, como nas outras grandes bacias hidrográficas brasileiras, são ainda incompletos e não existe consenso acerca do status taxonômico de muitas espécies listadas nesses levantamentos. Considerando o uso promissor do DNA barcoding como um sistema global de identificação de espécies, o presente estudo tem por meta realizar um inventário da ictiofauna da porção paulista do rio Paraíba do Sul e, simultaneamente compilar uma biblioteca de sequências referências para o DNA barcoding dos peixes encontrados. Foram obtidas e analisadas 354 sequências do gene Citocromo c Oxidase subunidade I (COI) pertencentes a 66 espécies da porção paulista do rio Paraíba do Sul. A distância genética K2P média encontrada entre indivíduos dentro das espécies desta bacia foi de 0,48%, e entre espécies dentro de um mesmo gênero de 9,87%. Cinco pares de espécies (10 espécies) apresentaram baixos valores de divergência genética interespecífica (<2%), porém todas puderam ser corretamente identificadas. Este estudo evidenciou que as espécies de peixes analisadas puderam ser identificadas de forma eficiente, através da utilização da sequência barcode gerando dados que podem fornecer subsídios para estudos posteriores desta fauna, além de contribuir com a iniciativa global de caracterizar as espécies de peixes do mundo de um ponto de vista molecular
Keywords: Peixe - Identificação; Ictiofauna - Inventarios; Ichthyofauna; Paraiba do Sul, Rio, Bacia